Antibacterial polylysine-containing hydrogels for hemostatic and wound healing applications: preparation methods, current advances and future perspectives - Pourshahrestani, Sara; Zeimaran, Ehsan; Fauzi, Mh Busra (Biomaterials Science, 2024)
The treatment of various types of wounds such as dermal wounds, multidrug resistant bacteria-infected wounds, and chronic diabetic wounds is one of the critical challenges facing healthcare systems. Delayed wound healing can impose a remarkable burden on patients and health care professionals. In this case, given their unique three-dimensional porous structure, biocompatibility, high hydrophilicity, capability to provide a moist environment while absorbing wound exudate, permeability to both gas and oxygen, and tunable mechanical properties, hydrogels with antibacterial function are one of the most promising candidates for wound healing applications. Polylysine is a cationic polymer with the advantages of inherent antibacterial properties, biodegradability, and biocompatibility. Therefore, its utilization to engineer antibacterial hydrogels for accelerating wound healing is of great interest. In this review, we initially discuss polylysine properties, and then focus on the most recent advances in polylysine-containing hydrogels (since 2016) prepared using various chemical and physical crosslinking methods for hemostasis and wound healing applications. Finally, the challenges and future directions in the engineering of these antibacterial hydrogels for wound healing are discussed.
CRIS-Team Scopus Importer:2024-07-12